Pengembangan Investasi Syariah Berbasis Fintech Di Era Digital - Paisal Rahmat; Marlian Arif Nasution; Fadhilah Hanum Lubis (Jurnal Investasi Islam, 2025)
This research aims to develop Islamic investment based on financial technology (fintech) in the digital era, with a focus on increasing financial inclusion, Islamic financial literacy, and developing innovative and efficient investment products. The research method used is a library approach, as well as secondary data analysis from the literature. Overall, this study shows that the development of fintech-based Islamic investment in the digital era requires the integration of sophisticated technology, increased Islamic financial literacy, adequate regulatory support and collaboration between industry players. The development of fintech-based Islamic investment has the potential to increase financial inclusion and provide better investment alternatives for people who want to invest in accordance with sharia principles